Characterization of French tourism in tourist destination Havana - Montesino Pérez, Alejandro; Valle Breña , María Karla; Guanche Díaz, Amanda; Hernández Flores, Yoan (Universidad Francisco de Paula Santander, 2025)
Tourism is a sector that benefits from demand studies and segmentation. The more specialized and personalized the services, the more attractive they become. In Cuba, the gradual development of tourism has made it one of the most important sectors of the country's economy. In this regard, it is necessary to understand the preferences of visitors arriving at the destination to modify and improve service delivery and design new tourism products. In this context, it has been decided to conduct research aimed at characterizing the demand of French tourists in the Havana destination. To achieve this, tools such as document review and surveys based on standardized and face-to-face interviews were used. The French tourist visiting Havana shows an interest in learning about history and culture, has a middle-high income, and the predominant age is slightly younger than the global average. This study advances the understanding of French tourist demand in Cuba and also provides a basis for the creation of effective tourism strategies tailored to the specificities of the local market.